Application of a Multi‐Camera Stereo DIC Set‐up to Assess Strain Fields in an Erichsen Test: Methodology and Validation. (18th February 2013) - Wang, Y.; Lava, P.; Coppieters, S.; Houtte, P. V.; Debruyne, D.
<x xml:space="preserve">Abstract</x> Abstract: A multi‐camera stereo digital image correlation (MC‐DIC) set‐up is presented to obtain full displacement and strain fields of a sheet‐metal specimen subjected to an Erichsen test. The set‐up is composed of several conventional stereo DIC systems (two camera set‐up), each of which tracks the deformation of an aspect of the specimen. The individual measurements, including the geometries and the displacements, are then converted to the same reference frame to integrate into a global view. Afterwards, the strain is calculated based on the composed displacement field. It is found that the geometry and the displacement fields of the bulged specimen are ideally stitched, and smooth strain fields are obtained. The influences of the reference frame transformation and the stitching procedure on the MC‐DIC measurement are investigated. A rigid motion test is performed to validate the displacement measurement. It is discussed that the global field is more reliable than the individual measurements for this test set‐up.